Lifestyle Weight-Loss Intervention Outcomes in Overweight and Obese Adults with Type 2 Diabetes: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Franz, Marion J.; Boucher, Jackie L.; Rutten-Ramos, Stephanie; VanWormer, Jeffrey J. (Journal of the Academy of Nutrition and Dietetics, 2015)
The majority of people with type 2 diabetes are overweight or obese, and weight loss is a recommended treatment strategy. A systematic review and meta-analysis was undertaken to answer the following primary question: In overweight or obese adults with type 2 diabetes, what are the outcomes on hemoglobin A1c (HbA1c) from lifestyle weight-loss interventions resulting in weight losses greater than or less than 5% at 12 months? Secondary questions are: What are the lipid (total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglycerides) and blood pressure (systolic and diastolic) outcomes from lifestyle weight-loss interventions resulting in weight losses greater than or less than 5% at 12 months? And, what are the weight and metabolic outcomes from differing amounts of macronutrients in weight-loss interventions? Inclusion criteria included randomized clinical trial implementing weight-loss interventions in overweight or obese adults with type 2 diabetes, minimum 12-month study duration, a 70% completion rate, and an HbA1c value reported at 12 months. Eleven trials (eight compared two weight-loss interventions and three compared a weight-loss intervention group with a usual care/control group) with 6,754 participants met study criteria. At 12 months, 17 study groups (8 categories of weight-loss intervention) reported weight loss <5% of initial weight (−3.2 kg [95% CI: −5.9, −0.6]). A meta-analysis of the weight-loss interventions reported nonsignificant beneficial effects on HbA1c, lipids, or blood pressure. Two study groups reported a weight loss of ≥5%: a Mediterranean-style diet implemented in newly diagnosed adults with type 2 diabetes and an intensive lifestyle intervention implemented in the Look AHEAD (Action for Health in Diabetes) trial. Both included regular physical activity and frequent contact with health professionals and reported significant beneficial effects on HbA1c, lipids, and blood pressure. Five trials (10 study groups) compared weight-loss interventions of differing amounts of macronutrients and reported nonsignificant differences in weight loss, HbA1c, lipids, and blood pressure. The majority of lifestyle weight-loss interventions in overweight or obese adults with type 2 diabetes resulted in weight loss <5% and did not result in beneficial metabolic outcomes. A weight loss of >5% appears necessary for beneficial effects on HbA1c, lipids, and blood pressure. Achieving this level of weight loss requires intense interventions, including energy restriction, regular physical activity, and frequent contact with health professionals. Weight loss for many overweight or obese individuals with type 2 diabetes might not be a realistic primary treatment strategy for improved glycemic control. Nutrition therapy for individuals with type 2 diabetes should encourage a healthful eating pattern, a reduced energy intake, regular physical activity, education, and support as primary treatment strategies.